An entomobryid collembolan (Hexapoda: Collembola) from the Lower Permian of Southern Africa - Rick, E. F. (Bernard Price Institute for Palaeontological Research, 1976)
Permobrya mirabilis gen. et sp. nov., recorded from carbonaceous shales of the Middle Ecca of southern Africa, is a rather large entomobryid collembolan. The specimen, preserved in lateral view, is complete except for the dentes and mucrones of the furcula and details of the claws which are not visible in the shale matrix. The species is surprisingly similar to Recent Collembola.
Main article
Keywords: entomobryid collembolan; Permian; Southern Africa